IMPLEMENTATION OF BILINGUAL LEARNING IN EARLY CHILDREN IN KINDERGARTEN MUHAMMAD SHODIQ SUMBERDUREN - Muniroh, Muniroh; Ni’mah, Mamluatun; DP, Terza Travelancya (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2023)
Implementation of Bilingual Learning in Early Childhood is very embedded in everyday life in anticipation of global competition. Children who are given bilingual learning from an early age will be able to compete with the outside world because they can learn foreign cultures that use English as a world language. This study aims to describe bilingual learning in early childhood at Muhammad Shodiq Sumberduren Kindergarten. Children who have two language skills or bilingualism will be able to master a second language such as mastering English and Arabic, or their mother tongue. The research results of bilingual learning at Muhammad Shodiq Sumberduren Kindergarten are not carried out by coercion but are carried out with fun activities such as singing and playing, as well as getting used to children's language in daily communication, the application of bilingual learning at Muhammad Shodiq Sumberduren Kindergarten Krucil Probolinggo shows that every child turns out to be able to develop language naturally. However, children's language development is also influenced by parents, the environment and the world of education, especially in learning two languages (bilingual).